PENGEMBANGAN PROGRAM PERHUTANAN SOSIAL BERBASIS PARTISIPASI MASYARAKAT DI HUTAN ADAT NEGERI HUKURILA - Alicia Grenid Lussy; Thomas M. Silaya; Marthina Tjoa (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
The management of customary forests is a strategic approach to integrating local knowledge and community traditions into natural resource management. Customary forests are not only essential for environmental sustainability but also hold significant social and cultural value for local communities. This study aims to examine the development of social forestry programs, analyze the level of community participation, and identify factors influencing community participation in the management of the Hukurila Customary Forest, Sirimau District, Ambon City. The research was conducted in October 2025 using a descriptive qualitative and quantitative approach. Data were collected through structured interviews with 30 households, key informants including customary leaders, village officials, and officers from the Social Forestry Agency, and analyzed using a Likert scale. The results indicate that the social forestry program has been implemented through the provision of Economic Productive Tools, particularly for sugar palm fruit (kolang-kaling) processing and the development of Bang Pesona, contributing to local economic improvement. The levels of community understanding and participation were categorized as high, especially during the planning and implementation stages, while participation in decision-making and evaluation remained moderate. Key supporting factors include the role of customary leaders, community knowledge, and trust in managing institutions, whereas limited economic incentives remain a major constraint.